Avaliação da liberação de íon fluoreto de cimentos ionoméricos antes e após a recarga e com proteção da superfície - Antunes, Débora Pinto [UNESP]; Antunes, Drusila Pinto; Matos, Renato Camargo; Kamozaki, Maria Beatriz Beber [UNESP]; Pagani, Clovis [UNESP]; Salgado, Ivone Oliveira (APESB (Associacao de Apoio a Pesquisa em Saude Bucal), 2013)
Objective: To evaluate fluoride ion release from two anhydrous glass ionomer cements (GICs) and two resin-modified GICs (RMGICs) before and after recharge with 2% neutral sodium fluoride for 4 min and after surface protection of the Maxxion R GIC with an adhesive system, a cavity varnish and a colorless nail polish. Method: A stainless steel 2x6 mm matrix was used for fabricating 5 specimens of each material, which were immersed in 5 mL of deionized water, renewed every 24 h. Measurements with a potentiometer were performed on days 1, 2, 9 and 17, in the 1st and 2nd phases, and the specimens were buffered with a TISAB III solution. In the 2nd phase, the specimens were subjected to recharge and immersed again in 5 mL of deionized water. In the 3rd phase, the GIC surfaces were protected and readings were made at 5 min, 24 h, 48 h and 72 h. Tukey's post-hoc and Student's t tests were used for statistical analyses (p<0.05). Results: There was statistically significant difference in the comparison between the 1st and 2nd phases for all materials, except at day 2 for Vidrion R and VitroFil LC. In the 3rd phase, it was observed that for all materials, comparison of the first 5 min with the other times revealed statistically significant differences among the means of fluoride ion release. In the comparison with the other times, both the varnish and the colorless nail polish presented statistically significant difference between 24 and 48 h as well as between 24 and 72 h. Conclusion: The anhydrous GICs were more effective in fluoride ion release and recharge compared with the RMGICs. Maxxion R presented a homogeneous and statistically significant behavior in both phases. All materials for surface protection were efficient and the colorless nail polish had the best behavior.
Fluoride ion release from glass ionomer cements before and after recharge and surface protection
Keywords: Dental cements; Dental materials; Glass ionomer cements